2016
DOI: 10.1055/s-0035-1571248
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Head and Neck Microvascular Reconstructive Strategy at an Academic Centre: An 18-Year Review

Abstract: Background A remarkable development through the evolution of free flap techniques has led to the modern reconstructive head and neck surgery. This study aimed to review experiences from head and neck free-flap reconstructions performed at our institution over an 18-year period. Methods Between 1995 and 2012, 594 free-flap operations were performed on 541 head and neck patients at the Department of Plastic Surgery, Helsinki University Hospital, Finland. We retrospectively recorded hospital chart data regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…When a lesion also involves the tongue, the optimal reconstructive method should combine satisfactory structural cosmesis with good restoration of function of speech and swallowing. Opinions around optimal flap choice continues to be divided a study by Husso et al (2) demonstrated that the number of different flap types and flap combinations increased between 1995 and 2012 from 15 to 24 in the 5 year periods analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…When a lesion also involves the tongue, the optimal reconstructive method should combine satisfactory structural cosmesis with good restoration of function of speech and swallowing. Opinions around optimal flap choice continues to be divided a study by Husso et al (2) demonstrated that the number of different flap types and flap combinations increased between 1995 and 2012 from 15 to 24 in the 5 year periods analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 2 flaps were nonviable, which is consistent with current national data. 5 , 7 , 24 , 25 Nine patients required feeding tube insertion during the course of admission. This highlights the importance of preoperative assessment of postoperative swallowing function and wound status to avoid unnecessary second surgeries and prolonged LOS.…”
Section: Discussionmentioning
confidence: 99%
“…However, our free flap results are consistent with the published experiences from other centers. 24 , 25 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…With recent advances in microsurgical techniques, MFTT is now performed with success rates at major centers consistently in excess of 95%, 1 even for elderly patients. 2,3 MFTT offers improved functional recovery 4 and greater improvement in postoperative quality of life when compared to locoregional flaps. 5 Due to these improvements, flaps with limited donor site morbidity, such as the anterior lateral thigh (ALT) flap, have been used with increasing frequency using less stringent indications.…”
Section: Introductionmentioning
confidence: 98%